PKM Sosialisasi Olahraga Bola Tangan di UKM SPORT STKIP YPUP Makassar - Muhammad Akbar Syafruddin; Andi Sahrul Jahrir; Achmad Karim (Universitas PGRI Semarang, 2021)
The purpose of this basic training stage is to provide a good basis for the SPORT UKM of STKIP YPUP Makassar students related to technical aspects, training mechanisms and training methods, psychology and morals as prerequisites for achieving good results through development, skills and character with a focus point on increase in basic skills and knowledge in handball games. Population and Sample of Community Service Handball UKM SPORT Student of STKIP YPUP Makassar, obtained by using total sampling technique. The application of training methods for handball technique skills at the Student Sport Unit of STKIP YPUP Makassar in 2021 can be accepted by the community and obtain a significant increase in basic techniques and knowledge of handball sports.Keywords: Basic Handball Techniques, Exercise Methods, Handball Socialization